Long-Term Evaluation of Biomarkers in the Czech Cohort of Gaucher Patients - Malinová, Věra; Poupětová, Helena; Řeboun, Martin; Dvořáková, Lenka; Reichmannová, Stella; Švandová, Ivana; Murgašová, Lenka; Kasper, David C; Magner, Martin (International journal of molecular sciences, 2023)
A personalized treatment decision for Gaucher disease (GD) patients should be based on relevant markers that are specific to GD, play a direct role in GD pathophysiology, exhibit low genetic variation, reflect the therapy, and can be used for all patients. Thirty-four GD patients treated with enzyme replacement therapy (ERT) or substrate reduction therapy (SRT) were analyzed for platelet count, chitotriosidase, and tartrate-resistant acid phosphatase activity in plasma samples, and quantitative measurement of Lyso-Gb1 was performed in dried blood spots. In our ERT and SRT study cohorts, plasma lyso-GL1 correlated significantly with chito-triosidase (ERT: r = 0.55, p < 0.001; SRT: r = 0.83, p < 0.001) and TRAP (ERT: r = 0.34, p < 0.001; SRT: r = 0.88, p < 0.001), irrespective of treatment method. A platelet count increase was associated with a Lyso-Gb1 decrease in both treatment groups (ERT: p = 0.021; SRT: p = 0.028). The association of Lyso-Gb1 with evaluated markers was stronger in the SRT cohort. Our results indicate that ERT and SRT in combination or in a switch manner could offer the potential of individual drug effectiveness for particular GD symptoms. Combination of the key biomarker of GD, Lyso-Gb1, with other biomarkers can offer improved response assessment to long-term therapy.
Keywords: Česká republika; enzymová substituční terapie; glucosylsphingosine; lyso-Gb1; počet trombocytů; Czech Republic; Gaucherova nemoc; chitotriosidase; Gaucher Disease; long term therapy; biologické markery; lidé; Platelet Count; Humans; Biomarkers; type 1 Gaucher disease; Enzyme Replacement Therapy